Human urogenital schistosomiasis in West and Sub-Saharan Africa migrants in Sardinia, Italy: A retrospective monocentric study - Nicholas Geremia; Andrea De Vito; Vincenzo Lai; Vito Fiore; Elija Princic; Paola Rappelli; Giordano Madeddu; Sergio Babudieri (Journal of Infection in Developing Countries)
Introduction: Schistosoma (S.) haematobium is the aetiological agent of urogenital schistosomiasis endemic in Sub-Saharan Africa and the Middle East. Microhaematuria is strongly associated with schistosomiasis diagnosis. Praziquantel (PZQ) is the treatment of choice.